INFLUENCE OF SERVICE QUALITY PERCEPTION TOWARDS SATISFACTION AND CUSTOMER’S LOYALTY: A RESEARCH ON CELLULAR PHONE PROVIDER IN WEST JAVA - Waseso Seguro (Jurnal Ilmiah Ekonomi Bisnis, 2009)
The decrease of consumer satisfaction and loyalty should be carefully interpreted since both determine the performance of cellular telecommunication service provider. Simultaneously, consumer perception of service quality, bounded factor and relational relationship quality are factors that influence costumer satisfaction and loyalty. Data are collected from 8 universities in Bandung. The study applies two research methods, that is quantitative method using Structural Equation Modeling (SEM) and qualitative method using Focus Group Discussion. Research results identify that the principal determinant factor for customer satisfaction and loyalty is consumer perception of service quality, whereas bounded factor indirectly affects customer satisfaction, it functions as moderating variable for the relationships between costumer perception of service quality and relational relationship quality with customer loyalty. Relational relationship quality also indirectly affects customer satisfaction. Perception of services and relational relationship quality have direct effect on customer loyalty.Keywords: customer satisfaction, loyalty, perception of services